Penyajian Kembali Laba oleh Perusahaan Publik di Indonesia - Dian Retnoasih; . Faisal (Jurnal Akuntansi dan Bisnis, 2009)
The objective of this research is to compare the firm characteristics between restate firm and non restate firm, and to evaluate the value relevance earnings restatement toward market value and non market value. A samples of 55 firms that restated earnings among 2003-2005, which is listed in Indonesia Stock Exchange. Sampling method that has been used is purposive sampling. This research use Wilcoxon signed ranks test for hypothesis 1 and ordinary least square for hypothesis 2 and 3. The results show that there is characteristic differences between restate firm and non restate firm in growth, liquidity, profitability and leverage. Restate firms have lower growth, higher liquidity, higher profitability and lower leverage that non restate firm. The result about value relevance is earnings restatement does not influence market value significantly but earnings restatement influences non market value (future earning change) significantly.